Empirical estimation of densities in NaCl-KCl-UCl3 and NaCl-KCl-YCl3 molten salts using Redlich-Kister expansion. (16th January 2022) - Agca, Can; McMurray, Jake W.
Graphical abstract: Highlights: Density of NaCl-KCl, NaCl-YCl3, KCl-YCl3, NaCl-UCl3 and KCl-UCl3 molten salts were modeled. Temperature and composition dependent Redlich-Kister expansion is used in the model. NaCl-KCl-UCl3 and NaCl-KCl-YCl3 molten salt densities were successfully estimated. Muggianu interpolation scheme was used to estimate the ternary molten salt densities. Abstract: Densities of molten KCl-NaCl-UCl3 and KCl-NaCl-YCl3 ternary systems have been estimated using a multidimensional Redlich-Kister model. Temperature and composition dependent Redlich-Kister functions have been used to generate binary interaction parameters in the outlined ternary salt systems. These binary interactions have been used in the extrapolation to ternary system densities. The results of the density extrapolations by Muggianu interpolation scheme provide agreement within 2–3% for the NaCl-KCl-YCl3 liquids and 11% in NaCl-KCl-UCl3 liquids compared to the available experimental data. Modeling NaCl-KCl-UCl3 molten phase density with a ternary interaction parameter improved the agreement within 4%. Thermophysical modeling used in this study has shown promising results for use in other material properties, such as viscosity, thermal conductivity, and heat capacity of the molten salts. Furthermore, the outlined modeling method applied in these specific molten salt ternaries can be used for quaternary or higher multicomponent molten salt systems.